Integrasi Mindfulness-Based Stress Reduction (MBSR) dengan Muhasabah sebagai Konsep Baru Menurunkan Kecemasan Diri Siswa - Tri Cahyono; Muhammad Faros Nabawi; Nurwulan Ardelia Asy Syifa (UIN Siber Syekh Nurjati Cirebon, 2025)
Anxiety is a psychological problem that is commonly faced by teenagers in Indonesia, which is often triggered by academic, social, and spiritual pressures. This research aims to develop a theoretical design that combines Mindfulness-Based Stress Reduction (MBSR) and muhasabah as a comprehensive approach in reducing anxiety in adolescents. Using the narrative review method, this study explores key elements in MBSR such as meditation, body scan, and yoga, which focuses on improving self-awareness and managing emotions, as well as combining them with muhasabah, which includes spiritual reflection, moral evaluation, and accountability to God. The results of the analysis show that this approach functions through two main mechanisms: (1) cognitive management that helps individuals recognize and control negative thoughts without excessive emotional reactions, and (2) improving spiritual well-being through moral reflection and strengthening spiritual responsibility. The proposed framework includes various stages, ranging from education, practical exercises, group reflection, to application in daily life. The findings of this study indicate that the combination of MBSR and delibation can be an effective approach to reduce anxiety, strengthen self-awareness, and improve the emotional and spiritual well-being of adolescents.